Incidencia de los fertilizantes nitrogenados en la producción de bacterias nitrificantes - Pineda Pineda, Teófilo Alberto (2010)
This essay at the shrimp farm property of Mr. Miguel's Pine, located in Port Jelí, canton Santa Rosa, in El Oro province. Later, it was carried out at the laboratories of the Faculty of Agropecuary Sciences belonging to the Technical University of Machala. The objective was to evaluate the higher bacterial increase of nitrifyng bacteria obtained during one month. Aireación was used only during the isolation. It was analyzed the possibility of carried macrocultivars of nitrifyng bacterias using as nutrient media the commercial nitrogenated fertilizers (ammonia nitrate, ammonia sulfphate and úrea) and a solution of oligoelementos, with three levels of calcium carbonate. The trial had for each one their steps experiment consisted of: 3 treatments, 2 blocks and 3 reapplications, giving a total of 18 experimental units or samples for each step. The obtained data were analyzed with an ANOVA of 2 ways of interaction to detect significant differences The inoculate for the cultivars was of 10 ml/l, obtained from the mix in equal parts of the bacteria isolated formerly (28 000 UFC/ml of BOA and of 86 000 UFC/ml of BON). The bacterial counting for all cultivars was carried out at 30 days at the Microbiology laboratory with the more probable number method (NMP). Levels of fertilizers ammonia nitrate and ammonia sulphate if they impact in the populational increment of nitrifyng bacterias. If interaction exists among the fertilizers ammonia nitrate, ammonia sulphate and the levels of calcium carbonate. The úrea levels affect the populational increment of nitrifyng bacterias. Interaction doesn't exist between the úrea levels and the levels of calcium carbonate. As a resume, the macro cultivation of nitrifyng bacteria is feasible to be carried out on working field conditios.